THE IMPACT OF MBG (MAKANAN BERGIZI GRATIS) PROGRAM TOWARDS STUDENT INTELLIGENCE IN INDONESIA: Dampak Program MBG (Makanan Bergizi Gratis) Terhadap Kecerdasan Siswa di Indonesia - I Gusti Ngurah Octova Seventilofa (Yayasan Al-Amin Qalbu, 2025)
The Free Nutritious Meals (MBG) program is a national policy implemented by the Indonesian government to improve students’ nutritional status as part of human capital development. This article aims to examine whether the MBG program has a positive impact on the intelligence and cognitive development of students in Indonesia. The study employs a literature review method, analyzing government reports, empirical research findings, and relevant national and international academic publications. The findings indicate that adequate nutritional intake provided through the MBG program contributes positively to students’ learning concentration, school attendance, learning motivation, and classroom engagement. These factors are essential prerequisites for cognitive development and intellectual potential. However, empirical evidence directly linking the MBG program to measurable increases in intelligence indicators, such as IQ scores or long-term academic achievement, remains limited due to the program’s recent implementation. In conclusion, the MBG program demonstrates a positive influence on conditions that support student intelligence, while further longitudinal research is needed to assess its direct impact on intellectual outcomes